Cyber ​​Security Survival Kit: Generation Z's Digital Survival Strategies - Cahyo Hermanto; Sarah Azhar; Septi Septi; Yunisva Yunisva; Siti Dini; Novi Novi; Adel Adel; Salsabilal Salsabilal; Risma Risma; Rismawati Rismawati; Ai Fitri; Arie Arie (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
The community service initiative, featuring academics and students from STMIK Mardira Indonesia, occurred at MA Persis Katapang to improve digital literacy, specifically in cybersecurity for Generation Z.  The swift advancement of information technology yields advantages while simultaneously presenting numerous cyber risks, particularly to young people engaged in the digital realm.  This curriculum seeks to provide students with the information and abilities necessary to identify, evade, and address cyber threats via the "Cyber Security Survival Kit" module.  The employed methods consist of a blend of seminars, practical workshops, and interactive simulations.  The outcomes of this activity demonstrated an enhancement in participants' comprehension of internet security protocols, password management, phishing threat recognition, and digital identity safeguarding.  This program raises awareness of the importance of cybersecurity and promotes safe digital practices among students.